Erythrina moths Terastia meticulosalis Guenée and Agathodes designalis Guenée - Andrei Sourakov (EDIS)
The little known Erythrina moths represent a remarkable case of niche partitioning. In Florida, these two species feed on plants of the genus Erythrina (Fabaceae), including the coral bean, Erythrina herbacea, which is native to North Central Florida and is frequently used as an ornamental. This 10-page fact sheet was written by Andrei Sourakov, and published by the UF Department of Entomology and Nematology, February 2012.